ANALISIS KINERJA KEUANGAN DENGAN RASIO PROFITABILITAS DAN PENGARUHNYA TERHADAP HARGA SAHAM PERUSAHAAN SEKTOR INDUSTRI DASAR DAN KIMIA SUB SEKTRO PULP & PAPER DI BURSA EFEK INDONESIA - Ramfineli, Ranne Hidayatika; Ibrahim, Mariaty (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This study aims to determine and analyze the influence of financial performance with profitability ratios which are used as independent variables, Gross Profit Margn (GPM), Return On Investmant (ROI), Return on Equity (ROE) and Earning Per Share (EPS). while being used as the dependent variable is the price of shares in Pulp & Paper Indonesia Stock Exchange.The data used in this research is secondary data, financial highlights (annual report) and performance summary. As for the company's data Pulp & Paper Tbk listed on the Stock Exchange for 3 years ie 2012, 2013, 2014. Sampling was done by purposive sampling. the sample used was 5 Companies Pulp & Paper Tbk. Classic assumption test in this study include tests multikoliniearitas, heterocedasticity test, test for normality. Analysis of data using multiple linear regression analysis, t test, and test the coefficient of determination. Analysis of data using multiple linear regression analysis with SPSS 19.The results showed that the analysis of the influence of financial performance with the profitability ratio on stock prices, namely GPM, ROI, ROE and EPS on sector companies Pulp & Paper Tbk are Partial (t test) no significant effect on stock prices. The results of the koefesiens determination (R2) of 0.420, which means that the variable contribution GPM, ROI, ROE and EPS on stock prices was 24.0%. While the remaining 58.0% is influenced by other variables not included in this modelKeywords: Financial Performance, Profitability Ratios, Stock Price